ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEUNGGULAN BERSAING UNTUK MENINGKATKAN KINERJA PERGURUAN TINGGI SWASTA (PTS) PADA UNIVERSITAS DI JAKARTA BARAT - Helena Sitorus (Universitas Mercu Buana, 2015)
Abstract. High competition among Private Higher Education at PrivateUniversities in West Jakarta requires competitive advantage and thereby enhancesperformance of Private Higher Education as seen from the number of studentachievement. This research was done by developing a model to examine andanalyze the effect of market orientation, program innovation, environmentaladaptability, promotion, and reputation on competitive advantage. The populationin this research is the head of study program as well as the structural officer ofPrivate University in West Jakarta and the sample taken is 123. Instrumentanalysis of data used is Structural Equation Modelling (SEM) in AMOS 21.0program. The result shows that market orientation, program innovation,promotion, and reputation has positive and significant effect on competitiveadvantage. Similarly, competitive advantage also has positive and significanteffect on performance of Private Higher Education. Environmental adaptabilityhas only positive but not significant effect on competitive advantage.The mostdominant factor affecting competitive advantage is reputation. This research statesa policy that needs to be done is focusing on the application of reputation,program innovation, market orientation, and promotion to achieve competitiveadvantage in enhanching performance of Private Higher Education.Keywords: competitive advantage, environmental adaptability, marketorientation, program innovation, promotion, performance, reputation.